Feasibility Testing of a Household Industry Food Production Certificate Using an Expert System with Forward Chaining Method - Ardiansah, Irfan; Efatmi, Fajri; Mardawati, Efri; Putri, Selly Harnesa (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2020)
Quality and safe food products are the basic right of every consumer, including food products produced by small and medium industries. Good food production is an important factor in meeting quality standards or food safety licensing requirements. In setting standards, the government also plays an important role in providing direction and assistance to small and medium industries on achieving the specified quality standards. During this time the process is still carried out in a conventional manner directly to the industry. This conventional process is still considered ineffective by seeing the low level of business actors’ knowledge of the standards for Good Food Production Practice (GFPP). So, with this lack of knowledge, business actors’ interest in making food licensing is low. This study designed the application of an expert system that stimulates and provides an illustration for a standards assessment of Good Food Production methods. This research was conducted using Object Oriented Programming (OOP) engineering method for program development and using forward chaining for reasoning methods. This research proved that the application of an expert system for licensing due diligence can function in accordance with standards set by the government.